Membentuk Kepribadian Anak Melalui Lembaga Kesejehateraan Sosial Anak Cilandak Barat - Anrian Muhammad Umar; Muhammad Sahrul (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out the main problems in parenting. the pattern of care provided and the inhibiting factors supporting child care at the al`khairiyah children's social welfare institution, west cilandak. this research uses qualitative methods, data collection techniques using the snow ball technique, and data collection obtained from the results. interviews, observations and documentation. data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. the results of the research found that the main problem in raising children is still the discovery of foster children who are lazy. the pattern of parenting applied to children by the west cilandak al`khairiyah child welfare institution takes a physical, emotional and social approach. to foster children and provides two types of education, namely formal education and religious education. in forming the personality of foster children, caregivers use a religious approach such as reciting the koran, reading the koran, wirid, prayers and teaching good morals. supporting factors in the parenting pattern at the al`khairiyah west cilandak children's social welfare institution are the background of caregivers who have mastered religious knowledge, supporting infrastructure, as well as assistance from donors and local community self-help. also the inhibiting factors are foster children who are lazy, irregular donors and the lack of caregivers at the al`khairiyah west cilandak children's social welfare institution.